Some appropriate anchorages for removable orthodontics appliance - Ardiansyah S. Pawinru; Dewiayu Dewang (Makassar Dental Journal, 2020)
Orthodontic movement of a tooth or group of teeth occurs due to the application of the force applied by active components and these acting forces always generate reciprocal forces of the same magnitude but opposite in direction which follows Newton’s third law. Basically, anchoring management aims to keep the force used light and increase anchoring resistance, so that the gear that is expected to move while the teeth that are not expected to move can be held or minimized. During treatment, anchorage loss must be detected immediately, the cause searched, and dealt with as soon as possible so that no more severe errors occur so that the treatment results can be as good as possible. The purpose of this paper is to examine how to manage anchoring problems in orthodontic treatment using removable appliance, especially active removable appliance so that treatment results achieve satisfactory results.